Tackling complexities in understanding the social determinants of health: the contribution of ethnographic research - Bandyopadhyay Mridula (BMC, 2011)
Abstract Objective The complexities inherent in understanding the social determinants of health are often not well-served by quantitative approaches. My aim is to show that well-designed and well-conducted ethnographic studies have an important contribution to make in this regard. Ethnographic research designs are a difficult but rigorous approach to research questions that require us to understand the complexity of people's social and cultural lives. Approach I draw on an ethnographic study to describe the complexities of studying maternal health in a rural area in India. I then show how the lessons learnt in that setting and context can be applied to studies done in very different settings. Results I show how ethnographic research depends for rigour on a theoretical framework for sample selection; why immersion in the community under study, and rapport building with research participants, is important to ensure rich and meaningful data; and how flexible approaches to data collection lead to the gradual emergence of an analysis based on intense cross-referencing with community views and thus a conclusion that explains the similarities and differences observed. Conclusion When using ethnographic research design it can be difficult to specify in advance the exact details of the study design. Researchers can encounter issues in the field that require them to change what they planned on doing. In rigorous ethnographic studies, the researcher in the field is the research instrument and needs to be well trained in the method. Implication Ethnographic research is challenging, but nevertheless provides a rewarding way of researching complex health problems that require an understanding of the social and cultural determinants of health.